Institutional capacities for the local implementation of the Peace Agreement with the FARC: the point on political participation in the Municipality of Ituango, Colombia (2019)
The purpose of this paper is to analyze the institutional dimension of the Municipal Council of Ituango, Antioquia (institutional capacities and normative competences), as well as the attitudinal dimension (perceptions, positions) of its councilors, for the implementation of point two of the referred Peace Agreement to political participation and democratic openness. An analytical-interpretative exercise is chosen that allows not only to provide a comprehensive approach to a collegiate government body such as the Council, but also to understand the diverse dynamics that constitute it, which in some way affect decision-making, in the programmatic orientations, the focus of the resources, among other topics.